Effect of Age on Selected Plasma Indices of Biochemical and Mineral Metabolism in Two Strains of Broiler Chickens - Arzour-Lakehal , Nedjoua; Benlatreche, Cherifa; Boukerrou, Abderrahmane; Siliart, Brigitte (International Journal of Poultry Science, 2015)
The aim of the study was to determine changes in plasma concentrations of 12 biochemical parameters of lipid, protein, carbohydrate and mineral metabolism in two strains of broiler chickens and to compare blood profile of the two groups. The investigation was conducted on 160 broiler chickens: 80 broilers Isa 15 strain and 80 broilers Arbor Acres strain. For the two strains, samples were held at 7, 14, 35 (59 days for Isa 15 strain, 57 days for Arbor Acres strain) and then analyzed. Most of the estimated parameters were age-dependent. Concentrations of plasma cholesterol and triglycerides showed a significant decrease along the experimental period (p